Eucalyptus ESTs involved in the production of 9-cis epoxycarotenoid dioxygenase, a regulatory enzyme of abscisic acid production - Guerrini, Iraê Amaral [UNESP]; Trigueiro, Rodrigo M. [UNESP]; Leite, Regina M. [UNESP]; Wilcken, Carlos Frederico [UNESP]; Velini, Edivaldo D. [UNESP]; Mori, Edson Seizo [UNESP]; Furtado, Edson Luiz [UNESP]; Marino, Celso L. [UNESP]; Maia, Ivan de Godoy [UNESP] (FapUNIFESP (SciELO), 2005)
Abscisic acid (ABA) regulates stress responses in plants, and genomic tools can help us to understand the mechanisms involved in that process. FAPESP, a Brazilian research foundation, in association with four private forestry companies, has established the FORESTs database (https://forests.esalq.usp.br). A search was carried out in the Eucalyptus expressed sequence tag database to find ESTs involved with 9-cis epoxycarotenoid dioxygenase (NCED), the regulatory enzyme for ABA biosynthesis, using the basic local BLAST alignment tool. We found four clusters (EGEZLV2206B11.g, EGJMWD2252H08.g, EGBFRT3107F10.g, and EGEQFB1200H10.g), which represent similar sequences of the gene that produces NCED. Data showed that the EGBFRT3107F10.g cluster was similar to the maize (Zea mays) NCED enzyme, while EGEZLV2206B11.g and EGJMWD2252H08.g clusters were similar to the avocado (Persea americana) NCED enzyme. All Eucalyptus clusters were expressed in several tissues, especially in flower buds, where ABA has a special participation during the floral development process. Copyright by the Brazilian Society of Genetics.
Keywords: Abscisic acid; Drought resistance; Eucalyptus EST; NCED; Water deficit; abscisic acid; dioxygenase; avocado; Brazil; controlled study; data analysis; data base; enzyme synthesis; Eucalyptus; expressed sequence tag; flower; flower development; forestry; FORESTs database; gene cluster; gene expression; gene sequence; genomics; hormone synthesis; maize; non profit organization; nonhuman; nucleotide sequence; plant stress; research; Persea americana; Zea mays